2021
DOI: 10.3389/fmed.2021.751529
|View full text |Cite
|
Sign up to set email alerts
|

Lipotoxic Proximal Tubular Injury: A Primary Event in Diabetic Kidney Disease

Abstract: The pathogenesis of diabetic nephropathy is a complex process that has a great relationship with lipotoxicity. Since the concept of “nephrotoxicity” was proposed, many studies have confirmed that lipotoxicity plays a significant role in the progression of diabetic nephropathy and causes various renal dysfunction. This review will make a brief summary of renal injury caused by lipotoxicity that occurs primarily and predominantly in renal tubules during diabetic progression, further leading to glomerular dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 94 publications
(144 reference statements)
0
11
0
Order By: Relevance
“…Lipid remodeling in the PT_S3 as identified in this study might provide an explanation to the role of this segment in the progression of kidney disease. Aberrant lipid metabolism has been recognized as primary event and progression factor in diabetic kidney disease 22 , 23 . PI lipid species give rise to polyphosphoinositides which are important signaling molecules involved in, among others, cell proliferation, vesicle trafficking and apoptosis 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Lipid remodeling in the PT_S3 as identified in this study might provide an explanation to the role of this segment in the progression of kidney disease. Aberrant lipid metabolism has been recognized as primary event and progression factor in diabetic kidney disease 22 , 23 . PI lipid species give rise to polyphosphoinositides which are important signaling molecules involved in, among others, cell proliferation, vesicle trafficking and apoptosis 24 .…”
Section: Discussionmentioning
confidence: 99%
“…This has been mainly described in tubules, and is frequently referred to as lipotoxicity in humans and rodents, as well as in vitro. (34,(40)(41)(42)(43)(44)(45)(46)(47) Furthermore, phosphorylation of GSK3β, as seen in the organoids, is known to be involved in high-glucose mediated lipid depositions in renal tubular cells. (47) A recent study of this kidney organoid model showed that, with the absence of CPT1, the proximal tubules fail to use the mitochondrial long-chain fatty acid metabolism (48), confirming our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose, lipid and hormone metabolism disorders caused by HG exposure may lead to the accumulation of advanced glycation end products (AGEs) and the activation of protein kinase C (PKC) (18)(19)(20)(21)(22). AGEs can activate related signaling pathways, such as the nuclear factor kappa-B (NF-kB) and transforming growth factor b (TGF-b) pathways, promote EMT/EndMT, and result in glomerular podocyte loss and progressive glomerulosclerosis (23)(24)(25)(26)(27).…”
Section: Metabolism Disordersmentioning
confidence: 99%